2001
DOI: 10.1016/s1534-5807(01)00085-5
|View full text |Cite
|
Sign up to set email alerts
|

A Hormonal Signaling Pathway Influencing C. elegans Metabolism, Reproductive Development, and Life Span

Abstract: During C. elegans development, animals must choose between reproductive growth or dauer diapause in response to sensory cues. Insulin/IGF-I and TGF-beta signaling converge on the orphan nuclear receptor daf-12 to mediate this choice. Here we show that daf-9 acts downstream of these inputs but upstream of daf-12. daf-9 and daf-12 mutants have similar larval defects and modulate insulin/IGF-I and gonadal signals that regulate adult life span. daf-9 encodes a cytochrome P450 related to vertebrate steroidogenic hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
509
1
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 355 publications
(530 citation statements)
references
References 55 publications
14
509
1
1
Order By: Relevance
“…The D. melanogaster cyp18a1 is also homologous to the Ceanorhabditis elegans (Maupas) gene daf-9, which regulates dauer formation, larval growth, and longevity (Gerisch et al 2001). Dauer formation in C. elegans is a type of dormancy that is similar to insect diapause at both the physiological and molecular level (Sim and Denlinger 2008), and in C. elegans daf-9 loss-of-function mutants form constitutive dauer larvae (Gerisch et al 2001, Jia et al 2002. As illustrated in Fig.…”
Section: Ae Albopictusmentioning
confidence: 99%
“…The D. melanogaster cyp18a1 is also homologous to the Ceanorhabditis elegans (Maupas) gene daf-9, which regulates dauer formation, larval growth, and longevity (Gerisch et al 2001). Dauer formation in C. elegans is a type of dormancy that is similar to insect diapause at both the physiological and molecular level (Sim and Denlinger 2008), and in C. elegans daf-9 loss-of-function mutants form constitutive dauer larvae (Gerisch et al 2001, Jia et al 2002. As illustrated in Fig.…”
Section: Ae Albopictusmentioning
confidence: 99%
“…Previous studies by us and other groups showed that CS affects larval development of C. elegans (Gerisch et al, 2001;Jeong et al, 2010). In the present study, we have identified genes likely responsible for the defects of larval development in CS condition using proteomic and RNAi analyses.…”
Section: Discussionmentioning
confidence: 82%
“…Caenorhabditis elegans is a cholesterol auxotroph, which requires exogenously supplied cholesterol for normal growth (Lozano et al, 1984). Cholesterol deprivation or starvation (CS) inhibits growth (Gerisch et al, 2001;Jeong et al, 2010). The effects accumulate with succeeding generations, with CS-mediated developmental defects worsening in the progeny until finally they are arrested at the larval stage (Jeong et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Here, it was demonstrated that lifelong reduction of somatic growth is not sufficient to increase the length of life. Instead, these findings support the concepts that integrate reproductive development, energy metabolism, and lifespan, which have already been demonstrated in worms and flies (Gerisch et al ., 2001; Flatt et al ., 2008). Imaginal morphogenesis protein‐late 2 (IMP‐L2), a protein homologous to MAC25 (IGFBP7) that binds to insulin in Drosophila, has also been demonstrated to increase lifespan (Honegger et al ., 2008; Alic et al ., 2011), and it was discussed that IGFBPs may play a role in mammalian aging.…”
Section: Discussionmentioning
confidence: 99%